Ultrafast plasma immersion strategy for rational modulation of oxygen-containing and amino groups in graphitic carbon nitride. (15th April 2020) - Kang, Shifei; He, Maofen; Chen, Mengya; Wang, Junjie; Zheng, Lulu; Chang, Xijiang; Duan, Huanan; Sun, Di; Dong, Mingdong; Cui, Lifeng
Abstract: The co-modulation of the oxygen-containing and amino groups in the polymeric semiconductor graphitic carbon nitride (g-CN) has increasingly become a common concern toward advanced catalysis, energy and biomedicine applications. The intensive understanding of the existence state of oxygen-containing and amino groups in the polymeric structure of g-CN and the controllable methods of modulating these groups is highly desirable. Herein, a rational industrially applicable plasma strategy was designed and applied for controllable modulation of oxygen-containing and amino groups in g-CN within 10 min. X-ray diffractometry, Fourier transform infrared spectrometry, and X-ray photoelectron spectroscopy results indicated that the oxygen-containing and amino groups were controllably introduced after plasma treatment. Transmission electron microscopy, atomic force microscopy and N2 adsorption-desorption measurements verified the ultra-thin and two-dimensional in-plane mesoporous morphology of the optimized g-CN-O-NH2 . As a result, the rational g–CN–O-NH2 performed well in Cr(VI) photoreduction, photocatalytic bacterial disinfection and inactivation of tumor cells. The remarkable extensively applicable photocatalytic activity can be ascribed to the fast charge carrier transfer benefiting from the enriched preferable internal edge sites and ideal joint effect of internal –NH2 and OH- groups, as confirmed by the significantly weakened PL fluorescence intensity and prolonged fluorescence lifetime of the excited states under visible light irradiation. This work provides an impressive industrially applicable strategy for the structure optimization and functional groups modulation of polymeric materials towards enhanced electronic and catalytic performances. Graphical abstract: Image 1 Highlights: The Modulation of oxygen-containing and amino groups in g-CN can be achieved by an ultrafast plasma strategy. The whole plasma treatment process can be completed within 10 min without any solvent, calcination or waste. The extensively applicable photocatalytic activity of g–CN–O-NH2 can be ascribed to the fast charge carrier transfer. The rational plasma strategy is industrially applicable and environmental-friendly.